Mouda, M., Djebabra, M., “A Dynamic Model Proposal for the Analysis of Work Procedures - M MOUDA; M DJBABRA (J Fail. Anal. and Preven, 2015)
This article aims to propose a model for analyzing work situations. In this context, we focus our interest on the simplification of procedures for working where the proposed model is used to analyze human behavior in response to non-compliance of work procedures. From this analysis, ways to improve work processes will be identified.